First report of heartworm (Dirofilaria immitis) infection in an imported dog in Lithuania - Sabūnas V.; Radzijevskaja J.; Sakalauskas P.; Paulauskas A. (Helminthologia, 2019)
Over the past decade, increasing numbers of autochthonous cases of heartworm infection have been reported in the countries of Eastern Europe where previously only imported cases were described. In this report we have described the first clinical case of Dirofilaria immitis infection in an imported dog in Lithuania.